2009
DOI: 10.1111/j.1365-246x.2009.04253.x
|View full text |Cite
|
Sign up to set email alerts
|

An ambiguity in attenuation scattering imaging

Abstract: S U M M A R YMigration constructs a subsurface image by mapping band-limited seismic data to reflectors in the Earth, given a background velocity model that describes the kinematics of the seismic waves. Classically, the reflectors correspond to impedance perturbations on length scales of the order of the seismic wavelength. The Born approximation of the visco-acoustic wave equation enables the computation of synthetic data for such a model. Migration then amounts to solving the linear inverse problem for pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Here, we will demonstrate that a similar statement holds for a 1D layered scattering model m(z) in a 3D homogeneous background. For that case, we showed earlier (Mulder and Hak, 2009) that we obtain approximately the same data for a model and its scaled, depth-weighted Hilbert transform. These data obey 6) with µ = m(z)/z.…”
Section: A Demigration For a 1d Scattering Modelmentioning
confidence: 56%
See 4 more Smart Citations
“…Here, we will demonstrate that a similar statement holds for a 1D layered scattering model m(z) in a 3D homogeneous background. For that case, we showed earlier (Mulder and Hak, 2009) that we obtain approximately the same data for a model and its scaled, depth-weighted Hilbert transform. These data obey 6) with µ = m(z)/z.…”
Section: A Demigration For a 1d Scattering Modelmentioning
confidence: 56%
“…For the constant-density acoustic case with the Born approximation, we found that the resolution function cannot unambiguously distinguish between perturbations in velocity or in the quality factor that describes attenuation for an acquisition geometry with sources and receivers at the surface and a constant background model. This ambiguity was described in detail for horizontally layered scatterers in an earlier paper (Mulder and Hak, 2009). Here, we observed a similar behaviour for a 2D scattering model: data generated in a constant background model for the resolution function of a point scatterer were nearly identical when either the real part of this resolution function was used as a scattering model or i times its imaginary part.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations